2020
DOI: 10.1038/s41598-020-61426-z
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Central Obesity and Outcomes of Adult In-hospital Cardiac Arrest: A Retrospective Cohort Study

Abstract: to investigate the association between central obesity and outcomes following in-hospital cardiac arrest (iHcA). A single-centred retrospective study was conducted. Adult patients that experienced IHCA during 2006-2015 were screened. Body mass index (BMI) was calculated at hospital admission. central obesity-related anthropometric parameters were measured by analysing computed tomography images. A total of 648 patients were included, with mean BMI of 23.0 kg/m 2. the proportions of BMI-defined obesity in this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“… , The type I reaction mostly occurs in the bacterial cell membrane through hydrogen extraction with unsaturated phospholipid molecules, and then, these molecules react with oxygen, leading to the formation of lipid peroxides, which break the structural integrity and increasingly change the ionic permeability of the cell membrane . In the type II reaction, 1 O 2 is directly generated from molecular oxygen, which is considered the most threatening ROS because it can immediately damage biological molecules, including enzymes, peptides, unsaturated lipids, and other cellular components, leading to bacterial killing. , …”
Section: Innovative Photosensitizers For Antibacterial Photodynamic T...mentioning
confidence: 99%
See 2 more Smart Citations
“… , The type I reaction mostly occurs in the bacterial cell membrane through hydrogen extraction with unsaturated phospholipid molecules, and then, these molecules react with oxygen, leading to the formation of lipid peroxides, which break the structural integrity and increasingly change the ionic permeability of the cell membrane . In the type II reaction, 1 O 2 is directly generated from molecular oxygen, which is considered the most threatening ROS because it can immediately damage biological molecules, including enzymes, peptides, unsaturated lipids, and other cellular components, leading to bacterial killing. , …”
Section: Innovative Photosensitizers For Antibacterial Photodynamic T...mentioning
confidence: 99%
“…Polyelectrolytes play a vital role in natural biological systems and human society . Thus, Tang et al reported an efficient synthetic method for in situ generation of azonia-containing polyelectrolytes ( 541 ) in a one-pot manner from using available nonionic monomers and inexpensive ionic species (Figure a) …”
Section: Innovative Photosensitizers For Antibacterial Photodynamic T...mentioning
confidence: 99%
See 1 more Smart Citation
“…Depending on the EMS policy, IO access may be used as the last resort for medications administration [ 18 , 21 , 23 , 24 ] because of its high success rate during CPR [ 7 ]. Characteristics of patients for whom IV access was difficult may be different from those for whom IV access is more easily established, such as higher proportions of obesity in the former, which by itself may be associated with worse outcomes [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some animal studies suggested that obesity is a potential factor that weakens the cell membrane by affecting membrane biomechanical properties [5,6]. Obesity is a state of excessive accumulation of adipose tissue within the body [7]. If excessive fat increases the saturation of fatty acyl chains in the sarcolemma, phospholipid packing density is also increased, leading to a rigid membrane [8].…”
Section: Introductionmentioning
confidence: 99%